Whey Protein Hydrolysate Increases Translocation of GLUT-4 to the Plasma Membrane Independent of Insulin in Wistar Rats - Morato, Priscila Neder (Public Library of Science, 2013)
Whey protein (WP) and whey protein hydrolysate (WPH) have the recognized capacity to increase glycogen stores. The objective of this study was to verify if consuming WP and WPH could also increase the concentration of the glucose transporters GLUT-1 and GLUT-4 in the plasma membrane (PM) of the muscle cells of sedentary and exercised animals. Forty-eight Wistar rats were divided into 6 groups (n = 8 per group), were treated and fed with experimental diets for 9 days as follows: a) control casein (CAS); b) WP; c) WPH; d) CAS exercised; e) WP exercised; and f) WPH exercised. After the experimental period, the animals were sacrificed, muscle GLUT-1 and GLUT-4, p85, Akt and phosphorylated Akt were analyzed by western blotting, and the glycogen, blood amino acids, insulin levels and biochemical health indicators were analyzed using standard methods. Consumption of WPH significantly increased the concentrations of GLUT-4 in the PM and glycogen, whereas the GLUT-1 and insulin levels and the health indicators showed no alterations. The physical exercise associated with consumption of WPH had favorable effects on glucose transport into muscle. These results should encourage new studies dealing with the potential of both WP and WPH for the treatment or prevention of type II diabetes, a disease in which there is reduced translocation of GLUT-4 to the plasma membrane.